2010
DOI: 10.3233/jad-2010-100780
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Enzymatic/Oxidative Stress-Driven Oxysterols in Amnestic Mild Cognitive Impairment Subtypes and Alzheimer's Disease

Abstract: Oxidative stress, which contributes to neuronal damage, is thought to be a pathophysiological mechanism of Alzheimer's disease (AD). Markers of oxidative stress may appear early in the preclinical, mild cognitive impairment (MCI) phase of AD. We investigated the interaction among enzymatic-derived oxysterols (24S-hydroxycholesterol and 27-hydroxycholesterol), markers of oxidative stress, including free radical-related oxysterols (7β-hydroxycholesterol and 7-ketocholesterol), and vitamin E in AD patients and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 53 publications
1
39
1
Order By: Relevance
“…However, it has been observed that, in glial cells, and especially around senile plaques, there is an ectopic induction of CYP46A1, leading to some 24-OH production, but without compensating for the decrease of that oxysterol (Bogdanovic et al, 2001; Brown et al, 2004). Another study, however, has found that plasma levels of 24-OH and 27-OH in AD patients are not significantly different from control values (Iuliano et al, 2010). A small fraction of total 24-OH excretion occurs via the CSF, and the 24-OH concentration is increased in the CSF of AD patients, probably reflecting neuronal damage and loss rather then metabolically active neuronal cells (Schönknecht et al, 2002; Leoni et al, 2004).…”
Section: The Involvement Of Oxysterols In Ad Pathogenesismentioning
confidence: 92%
“…However, it has been observed that, in glial cells, and especially around senile plaques, there is an ectopic induction of CYP46A1, leading to some 24-OH production, but without compensating for the decrease of that oxysterol (Bogdanovic et al, 2001; Brown et al, 2004). Another study, however, has found that plasma levels of 24-OH and 27-OH in AD patients are not significantly different from control values (Iuliano et al, 2010). A small fraction of total 24-OH excretion occurs via the CSF, and the 24-OH concentration is increased in the CSF of AD patients, probably reflecting neuronal damage and loss rather then metabolically active neuronal cells (Schönknecht et al, 2002; Leoni et al, 2004).…”
Section: The Involvement Of Oxysterols In Ad Pathogenesismentioning
confidence: 92%
“…Of the remaining 35 studies, 6 studies were excluded for irrelevant outcomes and 5 studies were excluded for no usable data. Thus, 24 studies were finally included into the meta-analysis [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35]. Among those 24 studies, 19 studies were published in English [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35] while the other 5 studies were published in Chinese [36][37][38][39][40]. Those 21 case-control studies included a total of 1128 cases of Alzheimer's disease and 2498 controls without Alzheimer's disease [14-24, 28-32, 36-40].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In only one study was the plasma concentrations of 24-OHC found to be significantly increased in patients with AD or vascular dementia, which would be in agreement with the hypothesis that neuronal damage could be associated with a higher turnover of neuronal membranes, which provides higher levels of cholesterol to be converted into 24-OHC [125]. Another study reports that plasma levels of 24-OHC in AD patients were not significantly different from those in control subjects [126]. However, more consistent findings reported that a reduction of plasma 24-OHC was correlated with the severity of dementia or the degree of brain atrophy [72,78].…”
Section: Plasma 24-ohc and Mri In Neurodegenerative Diseasesmentioning
confidence: 52%